Alterations in serum matrix metalloproteinases during different reproductive stages of Murrah buffaloes - KRUPAKARAN, R PRAKASH; BALAMURUGAN, T C; PANDIYAN, G D V; ARUNKUMAR, S; PERUMAL, P (The Indian Journal of Animal Sciences, 2015)
A comparative study on serum gelatinase was carried out in Murrah buffaloes. Healthy buffaloes (24), 3-6 year old were selected and divided into 4 groups, each comprising 6 animals (group 1: pregnant; group 2: estrus; group 3: anestrus; and group 4: regular cyclic). Blood samples were collected in heparinised vacutainer and immediately transported to the laboratory. These samples were centrifuged at 3,000 rpm for 15 min and serum was preserved at -20°C in deep freezer. The serum samples were subjected to gelatin zymography. In group 1, major bands at 220, 92 and 72kDa bands were observed. The 92kDa MMP-9 band was very prominent and its activity was 3 times higher than that of MMP-2 and also 72KDa of MMP-2 band was very prominent as compared to the human marker. The 220 kDa band appeared as doublet of pro and active forms and above the level of 92kDa band. Minor catalytic breakdown products of 135 kDa were also observed. Below the 92 kDa band, 82kDa active form of MMP-9 was also observed as a band. In group 2, bands were observed at 220, 92 and 72kDa. The activity of MMP-9 band was about half a time lesser than that of human marker MMP-9 (92kDa). All the 3 enzymes were found only in their proform. The level of expression of MMP2 (72kDa) was equal to that of human marker. The ratio of MMP-9 and MMP- 2 was about 2.5. In group 3, there is a very prominent band of 72kDa MMP-2 and a fainter band of 92kDa MMP-9 and the faintest band of 220kDa MMP-9 were observed. Among the 3 bands, the MMP-2 was very prominent and the ratio of MMP-9 and MMP-2 was 0.25. Finally, in group 4, three bands were observed at 220, 92 and at 72 kDa. The level of expression of MMP-9 was greater than MMP-2 and the ratio MMP-9/MMP-2 was about 1.25. It is concluded that MMP2 and MMP 9 was demonstrated in the serum of all the 4 groups. The level of MMP-9 expression was greater in estrus buffaloes as compared to that of regular cyclic buffaloes and it was lowest in anestrus buffaloes.